Bioethanol Mixture for Diesel Engines - Imomov, Sh.; Khakimov, B.; Nuritov, I.; Tagaev, V. (INTI International University, 2023)
In the article, the increase of environmental and epidemiological problems in parallel with the decrease of hydrocarbon fuel reserves, as well as the constant increase in the price of traditional energy resources in recent years, the increasing demand for renewable energy sources in the world, the increase in the demand for fuel mixtures, and the problems of updating the methods of their preparation, and the main fuels the fact that the application of bioethanol addition technology has led to an increase in the amount of water, it is dedicated to the solutions to accelerate the corrosion of metal. In addition, the article is devoted to determining the amount of bioethanol added to diesel fuel, mixing time and temperature depending on the parameters of density and viscosity in the formation of a mixture of diesel and bioethanol fuel.